Fakta Forensik yang Mengungkapkan Pembunuhan dalam Kasus Dugaan Kecelakaan: Laporan Kasus yang Menguak Kebenaran di Balik Pengakuan - Samudra, Edeline; Kusumaningrat, Donald Rinaldi (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 14 No 2 (2024): Indonesian Journal of Legal and Forensic Sciences, 2025)
Blunt force trauma is an action that causes injury to body tissues due to an impact with a blunt object. The most commonly affected areas are the head and neck, which can lead to death. Blunt force trauma resulting in death can be intentional or accidental, such as in cases of homicide. A 19-year-old male body was found lying face-up, covered by bushes. External examination revealed abrasions on the chest, left abdomen, and right cheek. Internal examination showed skull fractures starting from the front right side and extending in a linear pattern through the eye socket, left and right sides, and the back of the skull. There was a tear in the dura mater on the left side, causing brain extrusion and bleeding. Blunt trauma refers to injuries caused by impacts, falls, or physical assaults with blunt objects, influenced by acceleration and deceleration forces. Although it is often associated with motor vehicle accidents, the victim, found 2 meters away from his motorcycle, should have shown signs of secondary injuries from being thrown from the vehicle. However, the absence of injuries from being dragged on the road, or contact with gravel, dirt, or sand, and the lack of damage to the motorcycle raised suspicions of a potential homicide. Based on the presence of larvae, the time of death was estimated to be 3-4 days prior to discovery, suggesting the body had been moved and staged to resemble a traffic accident. The skull fractures and intracranial bleeding indicated that the head injury from a blunt object was the cause of death. Forensic examination plays a crucial role in identifying the cause of death. In this case, although initially suspected to be a motor vehicle accident, forensic findings revealed that the death was caused by blunt force trauma.